Evaluasi dan Perbaikan Proses Bisnis Proyek Palapa Ring (PARING) Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: Badan Aksesibilitas Telekomunikasi dan Informasi) - Anggara Cahya Nugraha; Buce Trias Hanggara; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Agency of Telecommunications and Information Accessibility (BAKTI) is an institution under the auspices of the Ministry of Communication and Informatics which functions to manage the financing and provision of telecommunications in Indonesia. BAKTI has a major work program to build telecommunications infrastructure in Indonesia, especially in the 3T regions (outermost, outermost, and disadvantaged). One of BAKTI's main work programs is the Palapa Ring Project (PARING). In implementing the PARING project, problems that are often found are miscommunication between stakeholders involved, there is no standard business process flow and only uses a command system, in addition to other problems that can be found when conducting analysis and evaluation of existing business processes. Therefore an analysis is needed in evaluating and improving business processes to find problems and maximize running business processes. In this research business process modeling is carried out with Business Process Modeling and Notation (BPMN), then an evaluation of activities in the business process is carried out using the Failure Mode and Effect Analysis (FMEA) method and recommendations are made to improve business processes using Business Process Improvement (BPI) using tools streamlining. Then the simulation is done and the duration of business process completion is slower than as-is business process up to 4.5% in the Open Tender process, and the duration of business process completion is faster than as-is business process up to 0.88% in the Development process Telecommunications PARING and 1,058% in the Restoration-Maintenance process